2022
DOI: 10.1227/neu.0000000000001850
|View full text |Cite
|
Sign up to set email alerts
|

Revascularization of Hemorrhagic Moyamoya Disease in a North American Cohort: The Role of Timing in Perioperative and Long-Term Outcomes

Abstract: BACKGROUND: Several East Asian studies have examined the role of revascularization in the context of hemorrhagic moyamoya disease (MMD) and found a decrease in postoperative rehemorrhage rates. To date, no data exist comparing revascularization with conservative management in North American patients with hemorrhagic MMD. OBJECTIVE: To compare the clinical outcomes of conservative management vs surgical revascularization for North American patients with hemorrhagic MMD and investigate the effect of revasculariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Recent studies reported that revascularization surgery for adult patients with ischemic MMD could improve both cerebral perfusion of middle cerebral artery territory and cognitive function (14,15). Other studies also indicated that revascularization surgery could also reduce the incidence of rebleeding for hemorrhagic MMD patients and improve long-term outcomes (3,16). However, there was still a high rate of perioperative complications of bypass surgery for MMD patients, such as ischemic stroke, cerebral hemorrhage, hyperperfusion syndrome, and seizure attack.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported that revascularization surgery for adult patients with ischemic MMD could improve both cerebral perfusion of middle cerebral artery territory and cognitive function (14,15). Other studies also indicated that revascularization surgery could also reduce the incidence of rebleeding for hemorrhagic MMD patients and improve long-term outcomes (3,16). However, there was still a high rate of perioperative complications of bypass surgery for MMD patients, such as ischemic stroke, cerebral hemorrhage, hyperperfusion syndrome, and seizure attack.…”
Section: Discussionmentioning
confidence: 99%